O spotkaniach literatury i komentarza w twórczości Witkacego - Górska, Irena (Przestrzenie Teorii, 2007)
In Witkacy’s works literature and commentary meet one another incessantly. On one pole a phenomenon of dramatising of theoretical texts, e.g. aesthetic sketches is situated, and on the other the trick of playing theory within own, and on the other a trick of playing theory within own dramaturgy. Both these procedures allow the writer to assume different roles, thus various attitudes towards his own and others' theories. They both make it that the boundaries of literature and commentary are blurred. This also happens when Witkacy transfers his activities literally onto the margin [Marginalia filozoficzne komentarza (Philosophical trifles)]. The philosophical discourse played there in various forms (also plastic ones) makes it that the commented text and the commentary achieve equal status. Such a procedure also shows that reading is a performative act, and that the margin is no longer a marginal place.